Self-Efficacy as a Moderating Variable The Effect of Organizational Change on Work Stress and Employee Performance in Islamic Banks - Rizqy Nur Aziz; Muhammad Zakiy (FIRM Journal of Management Studies, 2023)
The development of the Islamic banking industry makes the competition increasingly fierce. One strategy for dealing with this is through organizational change. In the Islamic banking industry in Indonesia, Bank Syariah Indonesia (BSI) is an example of a bank making organizational changes. The occurrence of organizational change in a company has an impact that is likely to increase employee work stress and reduce employee performance. To minimize this impact and support the success of organizational change, a strategy is needed in the form of efforts to increase employee self-efficacy or self-confidence. This study aims to determine the impact of organizational change on job stress and employee performance moderated by self-efficacy. Respondents in this study were employees of Bank Syariah Indonesia (BSI) with years of service before and after the merger. The research data collection process was carried out online with 160 employees and then analyzed using the Structural Equation Modeling (SEM) method through the SmartPLS 3.2 application. This study indicates that organizational change has a positive effect on work stress, and organizational change has no effect on employee performance. This study also proves that self-efficacy is able to moderate the effect of organizational change on employee performance. Therefore, employees need to increase self-efficacy to support the success of the organizational change process.